KONSEP PENDIDIKAN PERSPEKTIF GENDER MENURUT KH. HUSEIN MUHAMMAD - admin, admin; Fitriah, Fitriah (THORIQOTUNA: Jurnal Pendidikan Islam, 2021)
The background of this research arises when gender differences have given birth to differences in social roles. Sometimes these social roles are standardized by the community, so there is no opportunity for women or men to change roles. In Javanese tradition, this standardization of roles is expressed in many proverbs, for example, women are the conco wingking of the man who becomes her husband. He is a life partner whose role is always behind. This proverb also implies that women's duties are behind them. In Javanese culture, the term "back" does not only point to a direction but can also mean a room, namely the kitchen, which is usually located at the back and seems hidden and hidden. The existence of a patriarchal culture with the legitimacy of this religion, can also be seen clearly in the Islamic community in Java. In fact, its existence tends to strengthen the existence of Javanese Patriarchal culture. One of the means of religious education that is still quite intense in maintaining a masculine perspective in its religious view is pesantren. In fact, it is from pesantren that many kyai, ustadz or da'i are born who will then transform religious teachings and religiosity to the wider community. As a result, the religious teachings and religiosity of the community will not be much different from what has been taught in pesantren. This includes the patriarchal teachings of religion and religiosity. Over time, a positive response to the discourse of feminism has come from the Islamic boarding school ulema who, according to some parties, are considered old-fashioned, paternalistic, feudal and patriarchal. Even these traditionalist Muslims are considered conservative and suspicious of change. This is shown by the emergence of new ideas about Islamic feminism from the 'traditionalist Islam' group, KH. Husein Muhammad tried to open horizons of understanding on the root causes of injustice or discrimination against women in all aspects of life, social reality that shows the enactment of the discriminatory system, especially with regard to the relationship between men and women in the midst of the struggles of life and life, both in domestic and public spaces. This research focuses on the concept of KH. Husein Muhammad as a pesantren cleric who is open in the discourse of feminism and is involved in the world of education regarding gender perspective education related to equal opportunity, justice/equality and empowerment between men and women in education, and his position as a kyai or pesantren cleric in carrying out the process. gender perspective education in Islamic boarding schools as an Islamic educational institution.